Sequence similarity network reveals the imprints of major diversification events in the evolution of microbial life - Cheng, Shu; Karkar, Slim; Bapteste, Eric; Yee, Nathan; Falkowski, Paul; Bhattacharya, Debashish (Frontiers in Ecology and Evolution, 2014)
Ancient transitions, such as between life that evolved in a reducing versus an oxidizing atmosphere precipitated by the Great Oxygenation Event (GOE) ca. 2.4 billion years ago, fundamentally altered the space in which prokaryotes could derive metabolic energy. Despite fundamental changes in Earth’s redox state, there are very few comprehensive, proteome-wide analyses about the effects of these changes on gene content and evolution. Here, using a pan-proteome sequence similarity network applied to broadly sampled lifestyles of 84 prokaryotes that were categorized into four different redox groups (i.e., methanogens, obligate anaerobes, facultative anaerobes, and obligate aerobes), we reconstructed the genetic inventory of major respiratory communities. We show that a set of putative core homologs that is highly conserved in prokaryotic proteomes is characterized by the loss of canonical network connections and low conductance that correlates with differences in respiratory phenotypes. We suggest these different network patterns observed for different respiratory communities could be explained by two major evolutionary diversification events in the history of microbial life. The first event (M) is a divergence between methanogenesis and other anaerobic lifestyles in prokaryotes (archaebacteria and eubacteria). The second diversification event (OX) is from anaerobic to aerobic lifestyles that left a proteome-wide footprint among prokaryotes. Additional analyses revealed that oxidoreductase evolution played a central role in these two diversification events. Distinct cofactor binding domains were frequently recombined, allowing these enzymes to utilize increasingly oxidized substrates with high specificity.